Brit és amerikai részvétel a debreceni Nyári Egyetemen a II. világháború előtt - Lieli, Pál (Gerundium, 2011)
British and American Participation at the Debrecen International Summer School before World War Two. This survey focuses on a selected aspect of the history of a peculiar and in many respects unique initiative: the pre-World War One British and American ties of the Debrecen International Summer School, which was established in 1927. In doing so, the study firstly identifies by name those British and American guests who can be documented as having attended the Summer School as officially enrolled students;secondly, it follows up and evaluates those aspects of the teaching program which had a British or American relevance; and, in the third place, it supplies examples for how the International Summer School advertised itself in the English-speaking countries. The survey is concluded by an analysis of selected contemporaneous views formulated by the representatives of the university and of the Summer School with reference to the past and (then) presence of British/American and Hungarian ties.